Pola Asuh Religius Terhadap Pembentukan Identitas Gender pada Anak Laki-laki di Panti Asuhan Islam Media Kasih Putra Banda Aceh - Mubarok, Muhammad Syahrul; Sulastri, Ema; Yusliani, Hamdi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
Religious parenting is one of the various parenting approaches, this method can be a very effective approach in shaping gender identity in boys. This study aims to determine the methods, supporting factors and inhibiting factors, as well as the evaluation of religious parenting in shaping gender identity in boys at the Media Kasih Putra Islamic Orphanage in Banda Aceh. This type of research is field research with a qualitative descriptive qualitative approach. The sampling technique used a purposive sampling technique. Data collection methods were in-depth interviews, observation, documentation with data analysis techniques consisting of data reduction, data presentation, and drawing conclusions. The results of the study show that: 1) this religious parenting pattern uses 5 methods in shaping gender identity in boys at the orphanage, namely: the exemplary method, the habituation method, the attention method, the advice method and the punishment method; 2). Supporting factors include the role models of caregivers and Quran teachers, environmental influences within the orphanage, and peers. Inhibiting factors include external cultural influences (social media), the influence of the environment outside the orphanage, and innate traits. 3) Evaluation of religious parenting has a positive impact on the formation of gender identity in boys because all teachings are based on the Quran and Hadith. Therefore, it can be the right choice in educating children in today's digital era.